PENGEMBANGAN MEDIA DINDING KATA PADA PEMBELAJARAN BAHASA INDONESIA KEMAMPUAN MEMBACA PADA SISWA KELAS III SDN 05 PULAU PUNJUNG - Rendi Marlianda; Ana Novitasari; Yoli Silvia (STKIP Subang, 2024)
This research is motivated by the problem of students who still have difficulty reading and some still have difficulty reading. The aim of this research is to produce word wall learning media that is valid, practical and effective. The type of research used is development research or Research and Development (R&D) using the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation stage ( evaluation). The validity results of the word wall media were validated by 3 validators, namely material expert validation obtained a result of 86.1% which was categorized as very valid, linguist validation obtained a result of 83.3% which was categorized as very valid, media expert validation obtained a result of 81.66% which was categorized as very valid, The results of the practicality of word wall media through the teacher response questionnaire by class III teachers obtained a result of 100% which was categorized as very practical, while through the response questionnaire an average result of 93.54% was categorized as very practical. The effectiveness results obtained from the main school students' learning test results obtained an average of 95%, which was categorized as very effective.